Antimalarial efficacy of nine medicinal plants traditionally used by the Karens of Andaman and Nicobar Islands, India (Bangladesh Journal of Pharmacology, 2015)
The aim of this study was to assess the antimalarial activity of nine medicinal plants used by Karens of Andaman and Nicobar Islands, against Plasmodium falciparum chloroquine-sensitive MRC-2 isolate. The methanol extracts were obtained by cold percolation method and in vitro antimalarial activity was assessed using M-III method. The results indicated that out of nine plant species tested, four plants, viz., Z. spectabilis, S. wallichiana, C. pulcherrima and Amomum sp. demonstrated significant antimalarial activity (50% inhibitory concentration values were 5.5 ± 0.7, 12.0 ± 2.5, 14.6 ± 1.3 and 37.3 ± 2.5 ?g/mL respectively) with no toxicity effect on erythrocytes.